2018
DOI: 10.1038/s41598-018-27608-6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging in Biologically-Relevant Environments with AFM Using Stiff qPlus Sensors

Abstract: High-resolution imaging of soft biological samples with atomic force microscopy (AFM) is challenging because they must be imaged with small forces to prevent deformation. Typically, AFM of those samples is performed with soft silicon cantilevers (k ≈ 0.1–10 N/m) and optical detection in a liquid environment. We set up a new microscope that uses a stiff qPlus sensor (k ≥ 1 kN/m). Several complex biologically-relevant solutions are non-transparent, and even change their optical properties over time, such as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 56 publications
0
38
0
Order By: Relevance
“…We also showed molecular resolution of a lipid bilayer in a liquid environment, which is experimental evidence that we can image with high spatial resolution and low contact force. [25] However, there are still many ongoing challenges. How can we understand the ∆f (z) curve shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We also showed molecular resolution of a lipid bilayer in a liquid environment, which is experimental evidence that we can image with high spatial resolution and low contact force. [25] However, there are still many ongoing challenges. How can we understand the ∆f (z) curve shown in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The qPlus sensor is a stiff ( k = 1800 N/m) self-sensing quartz sensor with a resonance frequency around f 0 = 32 kHz. It has enabled unprecedented results in low-temperature AFM, such as the imaging of single pentacene molecules by Gross et al [12], intramolecular resolution of PTCDA at room temperature by Huber et al [13], as well as the capability to perform non-destructive measurements on sensitive biological samples in air and in a liquid [14]. Moreover, it has been shown that a qPlus AFM is capable of observing material dissolution [7,15].…”
Section: Methodsmentioning
confidence: 99%
“…Such high-resolution imaging in water with minimal deflection noise density (Fukuma and Jarvis, 2006) opened up the possibility of submolecular-scale imaging of liquid/solid interface as well as materials in liquid (Fukuma et al, 2005; Tracey et al, 2016). Lately, using stiff qPlus sensors with small amplitude was found to be able to obtain high Q-factors and image soft biological samples in liquid (Pürckhauer et al, 2018). The subsequent improvement of AFM in force sensitivity, operation speed and other basic performances will significantly broaden the application of AFM in liquid-environment.…”
Section: Perspectivementioning
confidence: 99%